(untitled) (Nigerian Journal of Technology, 2020)
Dear Readers, In this issue, some support staff had to come back to work; in the last issue they all had to work from home. We are again glad to publish the July 2020 issue online. Our issue statistics are shown in Table 1. The COVID-19 allowed many authors time to complete and submit their articles. So in this issue, we have 38 articles instead our normal 35. Some outstanding articles has been pre-scheduled for October 2020.